Awareness and Pattern of Sexually Transmitted Diseases: A Hospital Based Study - Thapa, Deeptara Pathak; Rana, Arnija (Nepal Journal of Dermatology, Venereology & Leprology, 2023)
Introduction: Sexually transmitted diseases (STDs) are infections that occurs due to sexual contact. There are various pathogens contributing for STDs. There is a rising trend of STDs globally, but actual reported cases are low due to low screening and reporting. Materials and Methods: This study was a prospective hospital-based study. Patients were included in the study according to the inclusion criteria. All data were recorded in a preset proforma. Routine laboratory investigations along with STD workup was done in patients. Results: A total of 62 patients were included in the study according to the inclusion criteria. The age ranged from 17-52years. There were 63% males and 37% females. The majority of patients were employed (60%). Regarding awareness about symptoms of STDs, the patients responded as Infertility in 22%, ulcers in 17%, followed by swelling, genital discharge, dyspareunia, and 24% gave multiple response. Regarding attitude about awareness of prevention of STDs, maximum patients (43%) responded that, through condom use, prevention of the STDs was possible. Out of the total patients 58% Spouse were the commonest partner in 27%. The patients presented with symptoms like urethral discharge in 26%, followed by genital ulcers, genital growth, mixed infections and vaginal discharge. The commonest diagnosis was Syphilis followed by Gonococcal urethritis, non-gonococcal urethritis, warts, Genital herpes, vulvovaginal candidiasis, molluscum contagiosum, and mixed infections. Conclusion: Syphilis is the most prevalent STD, according to the current study. Due to the dearth of knowledge regarding STDs, the STD patients, who visit our facility may only be the tip of the iceberg. It is necessary to spread awareness about STDs among individuals through social media and educational institutions, starting at the local level and moving up to the national level.